1997
DOI: 10.1097/00005792-199707000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Invasive Pneumococcal Infections: A Comparison Between Adults and Children

Abstract: A similar number of adults and children had invasive pneumococcal infection. There was male predominance, and different ethnic distribution between children and adults. The majority of adults (78%), had underlying diseases, but this was less frequent in children (24%). The presenting illness differed between adults and children. Complications of invasive pneumococcal infection occurred more frequently in adults than in children. The mortality rate in adults was 21.5%; in children, only 3.8%. The rate of penici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
25
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(33 citation statements)
references
References 38 publications
8
25
0
Order By: Relevance
“…Socioeconomic and geographical differences do not explain our results for a homogeneous patient population living in the same geographical area (11). Year-to-year variation in serotype distribution was not a factor in our study or in other studies of infections over time (20,30). Furthermore, antibiotic resistance due to preventive-antibiotic use in special-risk populations (26) and underlying immune system abnormalities such as those due to HIV infection (19) were also ruled out as an explanation for our results for different age groups.…”
Section: Discussionsupporting
confidence: 44%
See 2 more Smart Citations
“…Socioeconomic and geographical differences do not explain our results for a homogeneous patient population living in the same geographical area (11). Year-to-year variation in serotype distribution was not a factor in our study or in other studies of infections over time (20,30). Furthermore, antibiotic resistance due to preventive-antibiotic use in special-risk populations (26) and underlying immune system abnormalities such as those due to HIV infection (19) were also ruled out as an explanation for our results for different age groups.…”
Section: Discussionsupporting
confidence: 44%
“…Several studies have shown that serotype 3 is a frequent isolate from the respiratory tract (10,12) but an infrequent cause of invasive S. pneumoniae infections in children (17,20,23). In a recent study of invasive infections in children under 5 years of age in Santiago, Chile, serotype 3 caused only 3.3% of infections (three-pneumonias) (15).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite all rigorous definitions of pneumonia requiring the finding of a pulmonary infiltrate on a chest radiograph, 5,6,[12][13][14] in daily practice in patients with mild respiratory symptoms and a normal WBC count a chest radiograph will often not be ordered.…”
Section: Discussionmentioning
confidence: 99%
“…8,13 However, as many as 30% of patients might have an atypical illness, demonstrating the clinical variability of bacteraemic pneumonia. 7 As shown previously by Toikka et al 7 and confirmed in our study, 17% of children presented with normal WBC on admission.…”
Section: Paediatric Subgroupmentioning
confidence: 99%